Determination of characteristic errors and analysis of their dynamics utilizing recurrent information - Mikėnas , V.; Staniūnienė , G. (Psichologija, 1973)
The teaching of any branch of science must use the methods on the base of which it is possible to get and assimilate the necessary information. One of them is recording of recurrent information. The determination of characteristic errors in graphic works and dynamics of them recording recurrent information was analysed at the Electrical Engineering Faculty of the Kaunas Polytechnic Institute. The determination of characteristic errors and dynamics of them carrying out the tasks of various complexity of particular graphic work is shown in the article.